SIMULATION OF WELDING WORKBENCH DESIGN FOR STUDENTS' PRACTICAL WORK LEARNING USING DIGITAL HUMAN MODELING - Abryandoko, Eko Wahyu (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
The design of a welding workbench for the learning process must consider the risks of musculoskeletal disorders (WMSDs). This study aims to develop an ergonomic welding workbench design to reduce the risk of awkward working postures, such as excessive neck flexion and elevated arm positions during welding. Using a digital human modeling simulation approach with Catia V5 R21 software, the design was evaluated based on ergonomic parameters, including LBA, OWAS, CA, and RULA. This study fills a gap in ergonomic literature by providing a quantitative evaluation model tailored to the body postures of Indonesian students. The results reveal that Alternative Design I has superior specifications, including adjustable table height, permanent welding component clamps, and a table tilt angle of up to 30 degrees. The workbench reduces spinal stress and improves working comfort. OWAS analysis indicates reduced musculoskeletal system risks, while RULA evaluation demonstrates improved comfort levels with adjustable table heights. Practical applications of these findings include enhancing safety and efficiency in welding learning processes at educational institutions. The design improves students' productivity and health by providing a more ergonomic working environment. This research lays the groundwork for further development of adaptive ergonomic workbench designs tailored to local needs and recommends future studies to explore applying similar technologies in other fields.